Study on mechanical properties and microstructure of Al-SiC composite fabricated with different volume fraction of reinforcement - Muhammad Muzzammil, Mohd Zuki (2016)
Composite is generally a combination of two or more substance that has different physical or chemical properties. This research is focusing on metal matrix composites (MMCs) which are the incorporation of two different materials which is Aluminium and Silicon Carbide. MMCs usually consist of a low density metal, such as aluminium or magnesium, reinforced with particulate or fibers of a ceramic material, such as silicon carbide or graphite. Compared with unreinforced metals, MMCs offer higher specific strength and stiffness, higher operating temperature, and greater wear resistance, as well as the opportunity to tailor these properties for a particular application. This work represents the mechanical properties of the MMC fabricated with different volume fraction of reinforcement. These metal matrix composites are made up of aluminium as the base, and silicon carbide with different composition. The two compositions are 90% Aluminium + 10% Silicon Carbide and 80% Aluminium + 20% Silicon Carbide. The composites are fabricated using powder metallurgy techniques. The mechanical properties are determined by density and conducting a hardness test using Vickers Hardness Machine. The data of density and hardness test was calculated and compared to evaluate the effect of different volume fraction on the mechanical properties of MMCs. Moreover, the specimen was observed under the Optical Microscope to see the particles homogeneity and the effect it has on the mechanical properties. From the experimental analysis, it was obvious that 80% Aluminium + 20% Silicon Carbide has the highest density and hardness.